Environmental, genotypic and phenotypic correlations in a diallel cross of tomato cultivars - Miranda, João Eustáquio Cabral de; Maluf, Wilson Roberto; Campos, Joenes Pelúzio de (Pesquisa Agropecuaria Brasileira, 2014)
Six tomato cultivars (Lycopersicon esculentum Mill.) (Kada, Santa Antonio, São Sebastião, Ângela, Floradel and BGH 3470) and their fifteen possible F1 hybrids (reciprocal crosses excluded) were tested in 1977 in two locations - Viçosa (MG) and Ponte Nova (MG). Environmental, genotypic and phenotypic correlations were estimated for all possible pairs among the characters studied. The genetic component had stronger influence on the correlations than the environmental component, and the phenotype adequately reflected the genotype considered. Total and marketable yield, total number of fruit, number of clusters per plant, number of fruit per cluster are positively correlated with each other, and are negatively correlated with average weight of marketable fruit percent of early yield, percent of fruit cracking and number of locules per fruit.